The Impact of Ultimate Beneficial Owner Being Declared Bankrupt on Companies Under its Control - Reiza Ibrahim Saleh (IHSA Institute, 2022)
The existence of the ultimate beneficial owner became a concern after the issuance of Presidential Regulation No. 13 of 2018 concerning the Principle of Recognizing the Beneficial Owner to Prevent and Eradicate Money Laundering and Terrorism Financing as the efforts to prevent criminal acts from the company’s cash flow and trace the person who has control over the company. This paper uses a juridical-normative research method, examining the application of regulations of issues discussed in this paper. This paper discusses the impact if the ultimate beneficial owner is declared bankrupt by a court decision. From this paper, it can be concluded that the bankruptcy of the beneficial owner based on a court decision could have an impact on the shareholders composition company under their control.